Nosocomial Infection in Critically Ill Patient Receiving Stress Ulcer Prophylactic Drugs: Pneumonia in patients received ranitidine or sucralfate in ICU - Mojtahedzadeh, Mojtaba; Panahi, Yunes; Fazeli, Mohammadreza; Alizadeh, Somayeh; Naghizadeh, Mohammad Mehdi; Moharamzade, Yashar (Iranian Journal of Pharmaceutical Sciences, 2007)
Acidic pH of stomach, which is a normal physiological barrier against bacterial overgrowth, would increase by stress ulcer prophylaxis initiation and may lead to bacterial colonization and play as a source for infection transmission to the respiratory system which results in ventilator related pneumonia in patients admitted to the Intensive Care Units (ICUs). Therefore, finding methods to decrease the prevalence of aspiration pneumonia is an old debate. The current survey has been performed to evaluate the effect of ranitidine and sucralfate on bacterial colonization and development of aspiration pneumonia. This is a randomized clinical trial in two groups of fifteen critically ill patients older than 20 years of age admitted to the ICU of Sina Hospital, Tehran, Iran. All patients were under mechanical ventilation. One group had a regimen of 1 g sucralfate every 6 h by gavage and the other had 50 mg of intravenous ranitidine every 8 h with a loading dose of 100 mg. Gastric juice was sampled every 24 h for determining the pH and pathogen type. The gastric pH of ranitidine group was higher than of sucralfate group. Common microorganisms colonized in the gastric juice of patients were Pseudomonas, Staphylococcus aureus, Klebsiella, and Candida albicans. Aspiration pneumonia occurred in 4 patients in the ranitidine group and 2 patients in the sucralfate group. Similar frequency of colonized microorganisms in the two groups suggests that the effect of pH on bacterial colonization is negligible. Therefore, concurrent consumption of ranitidine and other acid lowering medications may lower the risk of aspiration pneumonia and stress ulcer in patients taking ranitidine. If it is the case, administration of ranitidine would be preferred to sucralfate.